2003
DOI: 10.1080/00016470310014166
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hydroxyapatite- and porous-coated stems in total hip replacement

Abstract: 24 patients underwent bilateral hip replacement, using the SROM modular system (Depuy Johnson & Johnson, MA, USA) with the porous-coated sleeve in one hip and an HA-coated sleeve in the other. 20 patients were followed for at least 4 years with clinical and radiographic evaluations. We found no difference between the two sides as regards the time of disappearance of thigh pain and hip scores. Radiographs showed a buttress sign in 18 HA-coated and 15 porous coated stems. There were no differences in the serial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…In the study by Coathup 34 which is mentioned above, no difference in wear between the concepts of fixation was detectable. This is also confirmed by Park 139 and Bauer 8 , who actually found less surface roughness in heads from HA coated THA, compared to porous coated and cemented THA.…”
Section: Hydroxyapatitesupporting
confidence: 76%
See 1 more Smart Citation
“…In the study by Coathup 34 which is mentioned above, no difference in wear between the concepts of fixation was detectable. This is also confirmed by Park 139 and Bauer 8 , who actually found less surface roughness in heads from HA coated THA, compared to porous coated and cemented THA.…”
Section: Hydroxyapatitesupporting
confidence: 76%
“…Several comparative clinical studies deny a beneficial role of HA in the medium-term perspective 139,140 while others suggest an improved fixation radiologically and an improved stress transfer with proximal HA-coating also after five years 41,157,162,189 . Donnelly et al 38 showed less radiolucency, less osteopenia and less osteolysis around the blasted Freeman hip with HA-coating compared to an only blasted prosthesis.…”
Section: Hydroxyapatitementioning
confidence: 99%
“…In several studies, HA-coated titanium stems were implanted on one side and identical stems without an HA coating were inserted on the opposite side. It was found that HA coating did not influence radiological results or clinical performance of these stems in the medium-term (Kim et al 2003, Park et al 2003). Recently published meta-analyses of HA-coated femoral stems in primary THA have also supported the notion that HA coating does not improve the survival of uncemented stems (Gandhi et al 2009, Goosen et al 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Although a fully HA-coated stem is expected to induce greater bone apposition, wider trabecular struts, and more connectivity compared with half HA-coated stems [2], or tapered corundum-blasted titanium stems [1], it is not clear if the HA coating has any role in better preserving bone stock, with studies showing good bony integration with uncemented nonbioactive surface implants [7,18].…”
Section: Discussionmentioning
confidence: 99%